2002
DOI: 10.1002/ijc.10472
|View full text |Cite
|
Sign up to set email alerts
|

Supra‐additive effect with concurrent paclitaxel and cisplatin in vulvar squamous cell carcinoma in vitro

Abstract: The effect of concurrent paclitaxel and cisplatin was tested in vitro in 5 vulvar squamous cell carcinoma (SCC) cell lines (UM-SCV-1A, -2, -4 and -7 and UT-SCV-3). Chemosensitivity was tested using the 96-well plate clonogenic assay. Paclitaxel concentrations used varied between 0.4 and 1.6 nM, and cisplatin concentrations varied between 0.1 and 0.9 g/ml. These drug concentrations are clinically achievable. Survival data were fitted to the LQ model, and the area under the curve (AUC) value was obtained with nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…To our knowledge, only a case report is available on the use of cisplatin as a single agent in vulvar carcinoma 30 . However, a number of in vitro studies have reported the effect of cisplatin on squamous cell carcinoma (SCC) including vulvar cancer 31–33 . Cisplatin primarily induces platination of DNA, leading to intrastrand and interstrand cross‐links 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only a case report is available on the use of cisplatin as a single agent in vulvar carcinoma 30 . However, a number of in vitro studies have reported the effect of cisplatin on squamous cell carcinoma (SCC) including vulvar cancer 31–33 . Cisplatin primarily induces platination of DNA, leading to intrastrand and interstrand cross‐links 34 .…”
Section: Discussionmentioning
confidence: 99%
“…30 However, a number of in vitro studies have reported the effect of cisplatin on squamous cell carcinoma (SCC) including vulvar cancer. [31][32][33] Cisplatin primarily induces platination of DNA, leading to intrastrand and interstrand cross-links. 34 Recently, it has been shown that cisplatin exerts its anticancer effect by inducing apoptosis through the activation of JNK and p38 cascades.…”
Section: Discussionmentioning
confidence: 99%
“…The PC combination for the treatment of MM patients has been investigated in two recently reported prospective trials (Table 3). 25, 26 The rationale for combining these agents has been: 1) platinum‐alkylating agents have been demonstrated to have a definite (though minor) degree of activity in melanoma16, 27–29; 2) taxanes were demonstrated in early clinical trials to have a minor activity in melanoma30–33; 3) in vitro and clinical data suggest synergy between these drugs when used in combination in a wide variety of tumors, including melanoma23, 24, 34–40; and 4) the toxicity profiles of these agents do not overlap. Early clinical trials testing the combination of paclitaxel with platinum agents in patients with a variety of diseases noted some responses among melanoma patients 23, 24, 27.…”
Section: Discussionmentioning
confidence: 99%
“…Raitanen et al [129] found that two of the three vulvar squamous carcinoma cell lines, having sublethal damage repair capacity, exhibited a trend toward loosing the repair capacity when exposed to TAX during the irradiation. In a further study, the combination of TAX and CDDP at concentrations that are clinically achievable (0.4-1.6 nM/ml and 0.1-0.9 g/ml, respectively) had a clear additive or synergistic cytotoxic effect on different vulvar squamous carcinoma cell lines [130]. Therefore, concurrent chemoradiation with TAX or TAX + CDDP deserves to be clinically assessed in patients with advanced vulvar cancer.…”
Section: Postoperative Adjuvant Treatment Of High-risk Patientsmentioning
confidence: 94%